PENGARUH LITERASI KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN : (Studi Pada UMKM Di Kecamatan Tambun Selatan) - Radina Amalia Maharani; Sumarno Manrejo; Bambang Prayogo (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this study is to examine and analyze the effect of financial literacy on the quality of financial statements. This research uses a quantitative research method, with primary data as the type and source of data. The population in this study consists of MSME actors in the South Tambun District. The sampling technique used is random sampling, and a total of 100 MSME actors were sampled. The analysis method used includes validity testing, reliability testing, determinant testing (R-Square), and hypothesis testing. The results of this study indicate that, partially, financial literacy has a positive effect on the quality of financial statements.